How Solid Is Economic Growth in the East African Community? - Gigineishvili, Nikoloz; Mauro, Paolo; Wang, Ke. (Washington, D.C. : International Monetary Fund, 2014)
Is rapid economic growth experienced by the East African Community during the past decade built on solid foundations? To gain some clues, we use a variety of newly-collected and existing data sources to analyze the structural transformation of output and exports, as well as indicators of their quality and sophistication. The move from agriculture to a wide range of other sectors-bodes well for continued growth, as do gradual improvements in quality. Yet, no clear winners on the production side seem to have emerged, to embed a durable comparative advantage in international markets. These observations may instill a note of caution against projecting rapid growth into the distant future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Kenya